Identification of Underground River Flow Using VLF (Very Low Frequency) and Geoelectricity at Karstic Area - Mahmuddin Marbun; Sismanto Sismanto; Zuhrahmi DE; Imran Tarique; Punhoon Khan Korai (CV FOUNDAE, 2023)
Mapping underground river karst areas in the karst mountains Cianjur, West Java, has been done using electromagnetic methods and Geoelectricity Dipole-dipole. Karst constituent formation region of West Java area is limestone, clay stone, limestone fractured, hard and dense limestone, and limestone containing no water (rigid). The aim of this research is to search for the existence of underground rivers using electromagnetic and geoelectric wave surveys. VLF method consists of 13 line with a length of 750 m and a 10 m spacing. Based on the results of data processing VLF method is known that the equivalent current density (ECD) demonstrated high conductive rocks. While Geoelectricity method consists of 10 line, the arrangement is a parallel between the distance of the line with a space of 20 m andlength between 300 m.VLF data interpretation results indicate anomalous equivalent current density (ECD) with high scores range from 180-300% indicated fractured limestones are occupied by water, while the resistivity anomaly from 0.45 to 7.40 Î©.m indicated as weathered limestone layers accumulated dengn clay stone, resistivity values 186-701 Î©.m, fractured limestones indicated that fills with water. With sizes ranging 5-15 m cavity, each line with nearly the same distance at a depth of approximately 15-105 m, there is a large cavity-cavity interconnected.